PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 002 JUMRAH KECAMATAN RIMBA MELINTANG - Harahap, Siti Hapsah; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Internal issue Background this research is student less comprehend the items of Mathematics Iesson. This Matter is seen from still lower the nya flatten - flatten the result learn the Mathematics namely 57,00 as well as still lower the nya of attainment KKM namely, from 20 student only 5 student or 25% a success reach the KKM. As for KKM specified by a school is 70. Problem of this research is " Whether/What applying model the Direct pembelajara can improve the result learn the Mathematics of student of class of V SD Negeri 002 Jumrah of Kecamatan Rimba Melintang ?".Bentuk research is form of Research of Class Action ( PTK). Hypothesis raised in this research is If applied by a Direct study model hence can improve the result learn the Mathematics of student of class of V SD Negeri 002 Jumrah Kecamatan Rimba Melintang of Regency Rokan Go downstream. This Research is done/conducted by as much 2 cycle by 6 is meeting times;rill, consisted of by 4 times items presentation and 2 times daily restating. After execution of study and data collecting. Data processed and analysed. Result of data analysis show at daily restating ( UH I) happened by the improvement flatten - flatten the result learn from elementary score 57,00 becoming 72,25 mounting 15,25 poin and from daily restating of I to daily restating of II ( UH II) happened by the improvement of equal to 17,75 so that become 90. Becoming by klasikal from elementary score to daily restating of II ( UH II) happened by the improvement 33 poin. Beside that is also happened by the make-up of complete activity of klasikal from score 25% at]restating of cycle I mount as much 30% so that percentage become 55% and at restating of cycle II mount as much 35% so that percentage become 90%. Is and also happened by the make-up of activity learn and student in each meeting. For the activity of learn at first meeting equal to 60% mounting at second meeting become 75% ( 15%), from meeting perdua to first meeting of cycle II become 85% ( 10%), and from first meeting to second meeting become 95% ( 10%). For the activity of student of at first meeting equal to 55% mounting to second meeting become 60% ( 10%), from second meeting to first meeting of cycle II become 75% ( 15%), and from first meeting to second meeting become 85% ( 10%). Becoming inferential that applying model the Direct study can improve the result learn the Mathematics of student of class of V SD Negeri 002 Jumrah Kecamatan Rimba Melintang.Keyword: Model The Direct Study, Result Of Learning Mathematics, PTK.2